Long working hours and all-cause mortality in China: A 26-year follow-up study - Huang, Yeen; Xiang, Yingping; Zhou, Wei; Li, Guanpeng; Zhao, Chengzhi; Zhang, Di; Fang, Shenying (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVES ': 'The relationship between long working hours and the risk of mortality has been debated in various countries. This study aimed to investigate the association between long working hours and all-cause mortality in a large population-based cohort in China. ' ' METHODS ': 'This retrospective cohort study (N=10 269) used a large, nationally representative data set [the China Health and Nutrition Surveys (CHNS)] from 1989 to 2015. Long working hours (≥55 hours per week) were compared to standard working hours (35–40 hours per week). The outcome measure was all-cause mortality. Hazard ratio (HR) for all-cause mortality was calculated from Cox proportional hazards regression models, with stratified analyses to assess differences in mortality risk among subgroups. ' ' RESULTS ': 'Among the participants, 411 deaths (3.52 per 1000 person-years) occurred during a median follow-up of 11.0 (range 4.0–18.0) years. After adjusting for covariates, long working hours were associated with a significantly increased risk of all-cause mortality [HR 1.49, 95% confidence intervals (CI) 1.02–2.18]. Stratified analyses revealed that this association was present only among men (HR 1.78, 95% CI 1.15–2.75) and smoking participants (HR 1.57, 95% CI 1.05–2.57). ' ' CONCLUSION ': 'This study provides evidence of an association between long working hours and all-cause mortality, which is specifically observed among men and smokers. Targeted interventions should be implemented to reduce excessive working hours and identify individuals at elevated risk, with support from labor organizations, policymakers, and employers.
Keywords: all-cause mortality; China; China Health and Nutrition Surveys; CHNS; death; follow-up study; long working hour; smoking